Optical microscale for antiferromagnetic S? ? optimistic conformable density - Tawfig, Ferdous M.; Körpinar, Talat; Körpinar, Zeliha; İnç, Mustafa (Elsevier B.V., 2024)
In this paper, we present spherical antiferromagnetic S? ? magnetic electromotive conformable ??,??,?? microscales in conformable deSitter space. Also, we get optical antiferromagnetic S? ?optimistic conformable ??,??,?? densities. Finally, we obtain geometric antiferromagnetic S? ?magnetic conformable ??,??,?? microscales in conformable deSitter space. © 2024 The Authors
Keywords: Conformable deSitter space; Microfluidic microscale; Optical antiferromagnetic model; Optimistic density